35 Years of Public Sector Reform in Central Europe - de Vries, Michiel S. author. aut Link
XXII, 223 p. 11 illus.
Keywords: This book examines public administration reforms in Central and Eastern Europe during the last three decades. After 1989, so-called socialist countries in Central and Eastern Europe started their transformation from centralistic to democratic societies. Their public administration systems changed dramatically, to adopt new norms and principles. Focusing on current EU-member states in the region, the book identifies similarities and differences in their public administrative reforms. Paying particular attention to three policy areas – education, health care, and local services – it assesses the historical roots of public administrative reforms, and how the legacy of being former members of the Warsaw Pact are still visible. The book argues that there are important differences between administrations in Central and Eastern European countries compared to older EU-member states, and that even within these countries, significant differences can be seen between developments and administrative reforms at the national and local level. It concludes by assessing the implications of these arguments for candidate EU members, and the complexities and pitfalls they might encounter in this process. Michiel S. de Vries is Professor of Public Administration at Kaunas University of Technology, Lithuania, and Emeritus Professor at Radboud University, the Netherlands. Juraj Nemec is Professor of Public Finance and Public Management, Masaryk University, Czechia. .